2018
DOI: 10.1590/0100-29452018297
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest quality of ‘Vitória’ pineapple as a function of the types of shoots and age of the plant for floral induction

Abstract: For the production and quality of pineapple fruits, the appropriate choice of the type of propagule to be used combined with the management of the ages for floral induction are important factors to reach the maximum of desirable characteristics that will define the success in the production of the pineapple and its good acceptance in the market. The objective of this research was to evaluate the post-harvest quality of fruits developed from different types of shoots and ages of floral induction of ‘Vitória’ pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
3
0
3
Order By: Relevance
“…These values are higher than those found in the fruits of 'Perola' and 'Smooth Cayenne' cultivars in studies by Reinhardt and Medina (1992) and similar to those found by Viana et al (2013) and Küster et al (2018) with the 'Vitoria' cultivar. On the other hand, Barker et al (2018) and Berilli et al (2014) reported higher average values of 16°Brix for 'Vitoria' cultivar. The soluble solids content observed in fruits from plants grown with complete solution is within the minimum parameter for commercialization of pineapple fruits, which are the soluble solids content of 12°Brix (BRASIL, 2002).…”
Section: Resultsmentioning
confidence: 80%
“…These values are higher than those found in the fruits of 'Perola' and 'Smooth Cayenne' cultivars in studies by Reinhardt and Medina (1992) and similar to those found by Viana et al (2013) and Küster et al (2018) with the 'Vitoria' cultivar. On the other hand, Barker et al (2018) and Berilli et al (2014) reported higher average values of 16°Brix for 'Vitoria' cultivar. The soluble solids content observed in fruits from plants grown with complete solution is within the minimum parameter for commercialization of pineapple fruits, which are the soluble solids content of 12°Brix (BRASIL, 2002).…”
Section: Resultsmentioning
confidence: 80%
“…O comprimento de frutos foi influenciado somente pelo cultivar, com destaque para o 'Pérola', o qual atingiu em média 20 cm, semelhante à obtida por Reinhardt et al (2002). A média obtida para o 'Vitória' foi superior à descrita em outros trabalhos recentes para a Região Litoral Norte e com indução floral menor um mês menor (dez meses após o plantio), Barker et al (2018) produziu frutos com 8,79 cm, enquanto Küster et al (2017) no cultivo sequeiro, variando o plantio em julho e setembro, obteve frutos com média de 11,51 cm. A variação é associada às condições edafoclimáticas no plantio e indução floral, que podem influenciar significativamente na qualidade dos frutos (Galeano et al, 2016;Santos et al, 2019).…”
Section: Resultsunclassified
“…A circunferência obtida para os frutos se mostrou inversamente proporcional em relação ao comprimento, sendo mais Research, Society andDevelopment, v. 10, n. 13, e449101321520, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i13.21520 determinante quando se compara cultivares, embora, entre as capinas haja diferença, os valores não são decisivos no momento da venda. Valores similares foram encontrados por Barker et al (2018).…”
Section: Resultsunclassified
“…The lower is the vigor of the plants at the time of floral induction, the lower will be the quality of fruit. In addition, the age of floral induction varies according to genotype and to the cultivation environment (Barker et al, 2018). For this reason, the ideal time to perform the floral induction should be identified to plan the control of the desirable harvesting season of fruit with market standard.…”
Section: Introductionmentioning
confidence: 99%